DEFORMATION MONITORING OF LARGE STRUCTURES BY GROUND-BASED SAR INTERFEROMETRY - Qiu, Zhiwei (Boletim de Ciências Geodésicas, 2016)
In this paper, a ground-based SAR interferometry technology was used to monitor major engineering. This technology has been recognized as a powerful tool for terrain monitoring and structural change detecting. Deformation monitoring for large project has been a hot issue among them. According to GBSAR interferometry principle and characteristics of IBIS system, the authors analysis the error sources of deformation monitoring, and experimentally extract atmospheric phase which should removed based on permanent scattered analysis. Atmospheric disturbance effect analysis is discussed in this paper, and an atmospheric correction method is proposed to remove atmospheric effect, then the effective displacement can be retrieved. Results from this approach have been compared with that from traditional method in this campaign, GBInSAR technology can be exploited successfully in deformation monitoring for major projects with high accuracy.